Moderating effect of government regulations on the relationship between cost recovery and financing of water investments in Nairobi peri-urban markets in Kenya - Kimani, Maina E.; Mouni, Gekara G.; Wanjau, Kenneth L.; Mung’atu, Joseph K. (My University, 2015)
Over the last 200 years, most water utilities have been publicly owned and managed. For this reason, public utility firms have been getting financial support from the government in form of subsidies in addition to the revenue they generate internally. However these water utilities have not been able to generate sufficient internal revenue to ensure sustainable financial investments. There has been low level of investment in the sector especially in peri-urban markets mainly due to poor cost recovery. The study explored moderating effect of government regulations on the relationship between cost recovery and financing of water investments in Kenya. The study adopted descriptive survey research design. A two stage sampling technique was used to obtain a sample population of 150 small scale water service providers. The study utilized self-administered questionnaire and content analysis for collecting data. SEM was used to analyse the relationship between cost recovery and financing of water investments.The findings of the study indicated that factors inhibiting cost recovery includes poor water pricing, low users’ charge and externalities. The recommended remedies to cost recovery includes cross-subsidization, gradual increase of user fees, and service improvement. The results of the study will be of great importance as it will contribute to greater understanding of various factors that inhibits cost recovery among water utilities and how these factors can be improved.
Keywords: Cost recovery; Financing; Peri-urban Markets; Safe drinking water